Organizational Decline and Turnaround - Trahms, Cheryl A.; Ndofor, Hermann Achidi; Sirmon, David G. (Journal of Management, 2013)
In the 20 years since the last review on organizational decline and turnaround, the scope of turnaround research has expanded dramatically; however, research on this phenomenon remains empirically and theoretically fragmented. Recent research has incorporated managerial cognition, strategic leadership, and stakeholder management and has identified simultaneous and complex resource-based actions beyond the two-stage model developed in the last review by Pearce and Robbins two decades ago. Thus, herein we build from Pearce and Robbins’ review by cataloguing the past 20 years of empirical evidence related to turnaround, developing a descriptive model of organizational decline and turnaround, and concluding with a theory-based research agenda for organizational decline and turnaround. In doing so, this article summarizes what we know about organizational decline and turnaround, and proposes what we need to study, while providing a theoretical road map to guide this future research.